The Stations of the Cross - Mumbai Archive Project Team (Jio Institute, 2024)
Our Lady of the Rosary church features Stations of the Cross. The Stations of the Cross, also known as the Way of Sorrows or the Via Crucis, are a series of scenes depicting Jesus Christ on the day of his crucifixion. The Stations of the Cross are tied to the Christian themes of repentance and mortification of the flesh.